Neuroendocrine-immune complex as the mirror of the state of exchange of nitrogenous metabolites at rats - Popovych, Igor; Kuchma, Igor; Ruzhylo, Sofiya; Zukow, Walery; Gozhenko, Anatoliy (Journal of Education, Health and Sport, 2021)
Background. Earlier we found that even in intact rats, certain parameters of nitrogenous metabolism fluctuate in a fairly wide range, which further expands in cases of prolonged water loads. Based on this, we have been created three groups that are homogeneous in the parameters of nitrogenous metabolism. We have been shown that each cluster is accompanied by a specific constellation of immune parameters. In this study, an attempt will be made to supplement the immune accompaniment of each constellation of nitrogenous metabolites with parameters of the autonomic nervous and endocrine systems. Material and methods. Experiment was performed on 60 healthy female Wistar rats, both intact and loaded with different mineral waters. Immune status was assessed by thymocytogram, splenocytogram, blood leukocytogram and immunocytogram, as well as by phagocytosis parameters of blood neutrophils and monocytes. The state of autonomous regulation assessed by HRV. The plasma levels of the hormones of adaptation: corticosterone, triiodothyronine and testosterone (by the <span class="17" style="font-family: ’Times New Roman’; color: #222222; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">ELISA) were determined as well as mineralocorticoid, calcitonin and parathyroid activity calculated by their electrolyte markers. Results. 9 neuro-endocrine and 17 immune parameters were identified, the set of which three clusters of nitrogen metabolism clearly differ from each other. The overall accuracy of the classification is 93,3%. Conclusion. The variety of states of exchange of nitrogenous metabolites is accompanied by specific constellations of 26 parameters of neuro-endocrine-immune complex.